Kondisi Ketahanan Pangan Provinsi Bengkulu (Aplikasi Food Security Quotient (FSQ) - Milda Okta Rolenza; Muhamad Mustopa Romdhon; Hariz Eko Wibowo; Eka Triana Yuniarsih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Regional food security reflects the availability of sufficient, equitable, stable, affordable, safe, and nutritious food. Food production in Bengkulu Province has decreased, such as rice production, which fell from 296,472 tons in 2019 to 277,310 tons in 2023, due to limited land and population growth. Income levels significantly affect people's access to food. People with low purchasing power or relatively small incomes will consume products at relatively lower prices and in smaller quantities. This directly affects the community's food quality because food consumption is not balanced with good quality. This study was conducted in October-November 2024 to analyze food security and the dynamics of food availability, access, and quality in Bengkulu. The research used secondary data from BPS 2019-2023 and related agencies. Samples were taken purposively, namely the regencies of South Bengkulu, Rejang Lebong, North Bengkulu, Kaur, Seluma, Mukomuko, Lebong, Kepahiang, Central Bengkulu, and Bengkulu City, for the sample analysis of access and quality indicators. In contrast, the availability indicator excluded Bengkulu City from the data analysis, considering that food availability in urban areas comes from inter-regional trade and is not influenced by local production. Data analysis used descriptive, correlational, and Food Security Quotient (FSQ) methods. The research found that the average food security index of Bengkulu Province in 2019-2023 was 1.07. Each food security indicator has an index value of 1.12 for the availability indicator, 1.13 for the food access indicator, and 0.97 for the food quality indicator.